Molecular docking of lutein as anti-photoaging agent in silico - Krisnayana, I Gede Bayu; Febyani, Putu Dewi; Sari, Ida Ayu Yadnyaningtias Permata; Laksmiani, Ni Putu Linda (Pharmacy Reports, 2021)
The accumulation of UV exposure resulted in the loss of skin elasticity, and the appearance of wrinkles on the skin is commonly known as photoaging. Matrix metalloproteinase-1 (MMP-1) is an enzyme that degrades type I and III fibrillar collagen. This study aims to determine the mechanism of MMP-1 inhibition by lutein, a carotenoid compound with high antioxidant activity, using in silico molecular docking. This study was conducted by optimization of lutein structure using HyperChem 8, preparation of MMP-1 (PDB ID: 966C) using Chimera 1.10.1, validation of the method, and docking lutein against MMP-1 using Autodock 4.2. The results showed lutein had binding energy of -12.28 kcal/mol, lower than RS2 native ligand (-10.83 kcal/mol). The hydrogen bond formed between lutein and MMP-1 through HIS228 residue. To conclude, lutein may be developed as an anti-photoaging agent by inhibiting the MMP-1.